Multicentre, retrospective study to assess long-term outcomes of chelator based treatment with trientine in Wilson disease patients withdrawn from therapy with d-penicillamine. Issue 9 (29th April 2022) - Weiss, Karl Heinz; Kruse, Carlot; Manolaki, Nina; Zuin, Massimo; Ferenci, Peter; van Scheppingen, Daphne; Wijnberg, Larissa; de Koning, Constance E.; Dhawan, Anil
Abstract : Objectives: Trientine dihydrochloride (TETA-2HCl) has been used for the treatment of Wilson disease for over 30 years. The current study was designed to systematically evaluate existing data to further define the long-term outcome of the efficacy and tolerability of TETA-2HCl in Wilson disease patients. Methods: Medical records of 77 Wilson disease patients were reviewed to collect data on hepatic and neurologic symptoms, copper (Cu) homeostasis and adverse events. Data were collected for 48 months after initiation of TETA-2HCl after withdrawal of D-penicillamine treatment. Results: Mean duration of TETA-2HCl treatment was 8 years (range 5 months–32.5 years). Over the course of TETA-2HCl treatment, 35% of patients had no hepatic symptoms whereas in 49.4% of patients, hepatic symptoms improved. They remained unchanged in 10.4% of patients and worsened in 5.2% of patients. No patients progressed to acute hepatic failure or necessity of a liver transplant. During TETA-2HCl treatment, 46.7% of patients had no neurologic symptoms; in 14.3% of patients, neurologic symptoms improved whereas in 36.4% of patients, they remained stable and worsened in 2.6% of patients. During the evaluation period, 12 patients discontinued TETA-2HCl treatment due to: anemia ( N = 1), inadequate hepatic response ( N = 2), switch to zinc treatment ( N = 8) and patient's decision to withdraw from treatment ( N = 1). Treatment-emergent adverse events were reported by 24.7% of the patients of which gastrointestinal disorders (9.1%) and nervous system disorders (5.2%) were most reported. Conclusions: TETA-2HCl is well-tolerated and effective in Wilson disease patients following the withdrawal of treatment with D-penicillamine. ClinicalTrials.gov Identifier : NCT02426905.